2018
DOI: 10.1007/s12192-017-0806-9
|View full text |Cite
|
Sign up to set email alerts
|

The small heat shock protein B8 (HSPB8) efficiently removes aggregating species of dipeptides produced in C9ORF72-related neurodegenerative diseases

Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are two neurodegenerative diseases in which similar pathogenic mechanisms are involved. Both diseases associate to the high propensity of specific misfolded proteins, like TDP-43 or FUS, to mislocalize and aggregate. This is partly due to their intrinsic biophysical properties and partly as a consequence of failure of the neuronal protein quality control (PQC) system. Several familial ALS/FTD cases are linked to an expansion of a repeated G4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 61 publications
4
77
0
Order By: Relevance
“…These results are similar to the toxicity reported for DPR proteins driven by artificial ATG start codons and where polyGR are more toxic than polyGA or polyGP (May et al , ; Mizielinska et al , ; Yamakawa et al , ; Lopez‐Gonzalez et al , , ; Schludi et al , ; Zhang et al , ; Choi et al , ). DPR proteins form protein aggregates that are degraded by autophagy (Cristofani et al , ). Indeed, bafilomycin A1‐mediated inhibition of autophagy enhances the accumulation of DPR proteins (Figs C and D, and EV3A and B).…”
Section: Resultsmentioning
confidence: 99%
“…These results are similar to the toxicity reported for DPR proteins driven by artificial ATG start codons and where polyGR are more toxic than polyGA or polyGP (May et al , ; Mizielinska et al , ; Yamakawa et al , ; Lopez‐Gonzalez et al , , ; Schludi et al , ; Zhang et al , ; Choi et al , ). DPR proteins form protein aggregates that are degraded by autophagy (Cristofani et al , ). Indeed, bafilomycin A1‐mediated inhibition of autophagy enhances the accumulation of DPR proteins (Figs C and D, and EV3A and B).…”
Section: Resultsmentioning
confidence: 99%
“…pTau can alter autophagy at multiple steps [48] and can trigger the formation of GVBs in vivo as well as in vitro [25]. Similarly, DPR aggregates, which alter autophagy pathways [26], were found within GVBs in neurons of ALS/FTD patients with C9orf72 expansion [15]. RBPs such as TDP-43 form aggregates in AD patient neurons and quite often granular pTDP-43 aggregates co-localize with GVBs in AD patient hippocampal neurons [29].…”
Section: Rna Binding Protein Homeostasis and Gvbsmentioning
confidence: 98%
“…Searching for factors that trigger GVD, Wiersma et al recently found that seeding of tau pathology initiates the formation of GVBs in tau P301 L and tau P301 S tg mice in vivo and in primary mouse neurons in vitro [25]. Furthermore, dipeptide repeat (DPR) aggregates, which are mainly processed via autophagy pathway [26] were found within GVBs in neurons of ALS/frontotemporal dementia (FTD) patients with C9orf72 expansion [15]. Similarly, recent studies have emphasized a functional interplay between ER function, autophagy, and RNA binding protein (RBP) homeostasis [27].…”
Section: Introductionmentioning
confidence: 99%
“…While HSPB8 was the most effective of the chaperones tested by Bruinsma et al in preventing α-synuclein fibrillization [381], purified HSPB8 is generally not a particularly effective chaperone in vitro, suggesting specificity for certain clients [190]. However, in the cellular context, HSPB8 has been shown to efficiently promote the autophagic clearance of misfolded and/or aggregation-prone proteins, including many disease-associated mutant proteins such as mutant SOD1, polyQ-expanded androgen receptor and huntingtin, TDP-43, and C9ORF72-derived dipeptide repeat proteins [15,397,400,409,411,[414][415][416][417][418][419].…”
Section: Hspb8mentioning
confidence: 99%